Current Concepts in Capsular Contracture: Pathophysiology, Prevention, and Management - Safran, Tyler; Nepon, Hillary; Chu, Carrie K.; Winocour, Sebastian; Murphy, Amanda M.; Davison, Peter G.; Dionisopolos, Tassos; Vorstenbosch, Joshua (Seminars in Plastic Surgery, 2021)
Over 400,000 women in the United States alone will have breast implant surgery each year. Although capsular contracture represents the most common complication of breast implant surgery, surgeons continue to debate the precise etiology. General agreement exists concerning the inflammatory origin of capsular fibrosis, but the inciting events triggering the inflammatory cascade appear to be multifactorial, making it difficult to predict why one patient may develop capsular contracture while another will not. Accordingly, researchers have explored many different surgical, biomaterial, and medical therapies to address these multiple factors in an attempt to prevent and treat capsular contracture. In the current paper, we aim to inform the reader on the most up-to-date understanding of the pathophysiology, prevention, and treatment of capsular contracture.
Keywords: capsular contracture; breast implant; foreign body reaction; inflammation